KOTA FESTIVAL DAN SKEMA KEBIJAKAN WISATA KOTA DI SURAKARTA - Akhmad Ramdhon; Heru Nugroho; Arie Sujito (Jurnal Analisa Sosiologi, 2020)
Tourism in Surakarta has a long dynamic in the attempt of contributing to the city development agenda. Based on tourism economic policy with MICE (Meeting, Incentive, Conference, Exhibition) tourism strategy, city tourism is supported with cultural festival. A series of festival agendas is used to promote city and MICE tourism as the city governance attempt as the part of tourism development in decentralization era.  This study explained art and cultural festival to support city tourism and its effect on the attempt of activating the economic. Primary data was collected with etnografi approach to a variety of city festival agendas, result of observation, in-depth interview, some related documents were review and analyzed. The result of research, Surakarta tourism policy along with cultural festival series becomes a cultural event supporting the tourist destination experiencing revitalization effort as well. The Spirit of Java becomes a policy node to support public participation in various festivals designed in regular event calendar. Tradition and history-based festival was recycled into creative works along with public enthusiasm in the platforms worked on grandiosely. The tourist visit rate affects the city’s economy and infrastructural development scheme, becoming the long-term city policy. Surakarta transforms gradually into new spaces to tourism industry with big challenge to ensure the preservation of city tradition, and conservation of culture. Keywords: City, Desentralization, City Tourism, Festival City AbstrakPariwisata di Kota Surakarta mempunyai dinamika yang panjang dalam upaya untuk berkontribusi pada agenda pembangunan kota. Berbasis kebijakan ekonomi wisata dengan strategi pengembangan wisata MICE (Meeting, Incentive, Conference, Exhibition) pariwisata kota yang ditopang festival budaya. Rangkaian  agenda festival  untuk mempromosikan kota dan wisata MICE sebagai upaya tata kelola kota sebagai bagian dari perkembangan pariwisata diera desentralisasi.  Studi ini menjelaskan festival seni budaya untuk menopang pariwisata kota dan dampaknya bagi upaya menggerakkan roda ekonomi.  Data primer diambil lewat pendekatan etnografis atas berbagai agenda festival kota, hasil observasi, in-depth interview, dan beberapa dokumen terkait direview dan dianalisis.  Hasil dari studi ini, kebijakan pariwisata Surakarta dengan rangkaian festival budaya menjadi event budaya sekaligus menopang destinasi wisata yang juga mengalami upaya revitalisasi. The Spirit of Java menjadi simpul kebijakan untuk mendorong keterlibatan publik dalam berbagai festival yang dirancang dalam kalender event reguler. Festival dengan basis tradisi dan sejarah yang didaur ulang kembali menjadi kerja-kerja kreatif bersama antusiasme publik di panggung-panggung yang digarap dengan megah.  Angka kunjungan wisatawan menjadi dampak bagi ekonomi kota dan skema pengembangan infrastruktur menjadi skema kebijakan kota jangka panjang. Kota Surakarta bertahap bertransformasi menjadi ruang-ruang baru bagi industri wisata dengan tantangan besar untuk memastikan kelestarian tradisi, dan budaya kota tetap terjaga dengan baik.Kata kunci : Kota, Desentralisasi, Wisata Kota, Kota Festival